Cosmetic and toiletry formulations. - Flick, Ernest W. (Cosmetic and toiletry formulations, 1999)
This book contains hundreds of cosmetic and toiletry formulations based on information received from numerous industrial companies and other organizations. Each formulation is indentified by a description of end use. The formulations contains a listing of each raw material, processing procedure, and source of the formula.